High Antigenicity for Treg Cells Confers Resistance to PD‐1 Blockade Therapy via High PD‐1 Expression in Treg Cells - Matsuura, Hiroaki; Ishino, Takamasa; Ninomiya, Toshifumi; Ninomiya, Kiichiro; Tachibana, Kota; Honobe‐Tabuchi, Akiko; Muto, Yoshinori; Inozume, Takashi; Ueda, Youki; Ohashi, Kadoaki; Maeda, Yoshinobu; Nagasaki, Joji; et al. (Cancer science, 2025)
ABSTRACT Regulatory T (Treg) cells have an immunosuppressive function, and programmed death‐1 (PD‐1)‐expressing Treg cells reportedly induce resistance to PD‐1 blockade therapies through their reactivation. However, the effects of antigenicity on PD‐1 expression in Treg cells and the resistance to PD‐1 blockade therapy remain unclear. Here, we show that Treg cells gain high PD‐1 expression through an antigen with high antigenicity. Additionally, tumors with high antigenicity for Treg cells were resistant to PD‐1 blockade in vivo due to PD‐1+ Treg‐cell infiltration. Because such PD‐1+ Treg cells have high cytotoxic T lymphocyte antigen (CTLA)‐4 expression, resistance could be overcome by combination with an anti‐CTLA‐4 monoclonal antibody (mAb). Patients who responded to combination therapy with anti‐PD‐1 and anti‐CTLA‐4 mAbs sequentially after primary resistance to PD‐1 blockade monotherapy showed high Treg cell infiltration. We propose that the high antigenicity of Treg cells confers resistance to PD‐1 blockade therapy via high PD‐1 expression in Treg cells, which can be overcome by combination therapy with an anti‐CTLA‐4 mAb. High antigenicity of Treg cells confers resistance to anti‐PD‐1 mAb monotherapy via high PD‐1 expression in Treg cells. Resistance to anti‐PD‐1 mAb monotherapy via high PD‐1 expression in Treg cells can be overcome by combination therapy with an anti‐CTLA‐4 mAb. PD‐1+ Treg cells in the TME and Treg cell antigens may be predictive biomarkers for combination therapy with anti‐PD‐1 and anti‐CTLA‐4 mAbs.